2020
DOI: 10.3390/molecules25071634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Parameters on the Extraction of Grape Seed Oil Obtained by Low Pressure and Supercritical Fluid Extraction

Abstract: Grape seeds are an important byproduct from the grape process. The objective of this work was to evaluate the effect of experimental parameters (temperature and time of pretreatment with ultrasound) to obtain grape seed oil using low pressure (Soxhlet-Sox and Bligh Dyer-BD) and high pressure (supercritical carbon dioxide-SFE) methods. The best condition for pretreatment of samples was 30 min of sonication at 30 °C before extraction by Sox or BD. Ultrasound pretreatment was efficient to increase oil extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 85 publications
0
34
0
Order By: Relevance
“…Based on the increase or decrease of temperature, the solubility of extract change, and the extracting agent can be separated from the solvent (Baiano, 2014;Barba et al, 2016). These facts were shown by several authors when applying the SFE to grape by-products (de Souza et al, 2020;Ghafoor, Park, & Choi, 2010;Manna et al, 2015).…”
Section: Supercritical Fluid Extraction (Sfe) Sc-co2 Extractionmentioning
confidence: 86%
See 1 more Smart Citation
“…Based on the increase or decrease of temperature, the solubility of extract change, and the extracting agent can be separated from the solvent (Baiano, 2014;Barba et al, 2016). These facts were shown by several authors when applying the SFE to grape by-products (de Souza et al, 2020;Ghafoor, Park, & Choi, 2010;Manna et al, 2015).…”
Section: Supercritical Fluid Extraction (Sfe) Sc-co2 Extractionmentioning
confidence: 86%
“…Vitamin E, also known as tocopherol, is a constituent of grape seeds, varying from 10 to 20% of DM, and it depends on the grape variety, origin, and environmental growing conditions (de Souza et al, 2020). It acts as a lipid-soluble chain-breaking antioxidant, being involved in the protection of polyunsaturated fatty acids and lipoproteins from lipid peroxidation, preserving the integrity of biological membranes, lipoproteins, and lipid stores against oxidation (Barba et al, 2016;de Souza et al, 2020;Maroun et al, 2017). These mechanisms relate to the prevention of many diseases, such as atherosclerosis, cancer, aging, cataracts.…”
Section: Vitaminsmentioning
confidence: 99%
“…The methodology described by Bligh and Dyer (1989) is commonly used for extracting oil from fruit seeds (Batias‐Montes et al, 2020; Rotta et al, 2018; Souza et al, 2020; Wannes & Marzouk, 2016). In this methodology, a binary mixture of chloroform is used to extract neutral and polar lipids (Iverson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several extraction techniques have been studied in order to optimize the recovery of existing compounds in food or by-products (seed, bagasse, skin, stalk), including ultrasound-assisted extraction (UAE) [ 19 , 20 ] and the use of several enzymes to degrade the vegetal matrix [ 21 , 22 ]. This method consists of the emission of ultrasonic waves that provide pressure variation in the liquid and, at the same time, cavitation capable of generating shear forces and microbubbles responsible for greater surface erosion, fragmentation and mass transfer [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound technique is considered green technology because it requires less solvent and energy consumption, reduces the time for the process and requires moderate temperatures, which favors thermo-sensitive compounds, compared to conventional extractions, such as solid−liquid and Soxhlet [ 24 ]. Previous studies showed better results of bioactive compound extraction in grape by-products through the UAE application over conventional techniques [ 19 , 20 ]. Despite this, there is little information about the effect of UAE extraction using different conditions on the polyphenol compound content, and antioxidant capacity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%